1998
DOI: 10.1520/jfs14350j
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Repeated Psychophysiological Detection of Deception Testing

Abstract: This study was designed to determine how reliable and valid a Zone Comparison PDD test is when the same individuals are administered the same test on two different occasions. Seventy-two subjects were used in an analog mock crime study using a Zone Comparison test format. Thirty-six subjects were randomly assigned to "innocent" and thirty-six to "guilty" programmed conditions. In addition, each subject was assigned to either an "accurate", "inaccurate", or "no" feedback treatment group. The overall accuracy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…The three chart rule may have been adopted because it was believed that data produced after three question series was less diagnostic or useful due to habituation (Balloun & Holmes, 1979;Suzuki & Hikita, 1964). However, recent work has shown that the strength and diagnosticity of the data signals do not degrade with additional presentations (Dollins, Cestaro, & Pettit, 1998;Elaad & Ben-Shakhar, 1997;Nakayama & Kizaki, 1990;Yankee & Grimsley, 1987) . The Utah approach uses either three or five charts.…”
Section: Chart Usage Rulesmentioning
confidence: 99%
“…The three chart rule may have been adopted because it was believed that data produced after three question series was less diagnostic or useful due to habituation (Balloun & Holmes, 1979;Suzuki & Hikita, 1964). However, recent work has shown that the strength and diagnosticity of the data signals do not degrade with additional presentations (Dollins, Cestaro, & Pettit, 1998;Elaad & Ben-Shakhar, 1997;Nakayama & Kizaki, 1990;Yankee & Grimsley, 1987) . The Utah approach uses either three or five charts.…”
Section: Chart Usage Rulesmentioning
confidence: 99%
“…Maintenance polygraphs should be used frequently when the supervision team has reason to believe the offender may be at risk of reoffending. The Department of Defense Polygraph Institute (Dollins, Cestaro, & Pettit, 1995) reported the efficacy of repeated polygraph testing for the Zone Comparison Test, so concerns about the habituation of offenders to frequent polygraphs may be unfounded.…”
Section: Research Findingsmentioning
confidence: 99%
“…For this reason alone, dependence on behavioral performance measures may not provide a clear or reliable answer to the question of whether or not lexicosemantic/prosodic incongruence causes cognitive conflict. Furthermore, whereas we may mask or alter our true behavioral reactions via conscious choice, it is much more difficult to consciously choose to alter our psychophysiological reactions (Dollins, Cestaro, & Pettit, 1998). These may therefore represent a more objective index of the response to cognitive conflict.…”
Section: Previous Applications Of Related Tasksmentioning
confidence: 99%